ทัศนคติต่อวิชาชีพพยาบาลของเจนเนอเรชันซี: กรณีศึกษาโรงเรียนมัธยมศึกษาแห่งหนึ่ง - อ่อนศรี, ปราณี (Journal of The Royal Thai Army Nurses, 2017)
การวิจัยครั้งนี้การวิจัยเชิงพรรณนา เพื่อศึกษาทัศนคติต่อวิชาชีพพยาบาลของเจนเนอเรชันซี และเปรียบเทียบทัศนคติต่อวิชาชีพพยาบาลของกลุ่มตัวอย่างที่แผนการเรียนแตกต่างกัน กลุ่มตัวอย่างเป็นนักเรียนชั้นมัธยมศึกษาปีที่ 6 ปีการศึกษา 2559 จำนวน 251 คน เครื่องมือที่ใช้คือ แบบสอบถามทัศนคติต่อวิชาชีพพยาบาล มีค่าสัมประสิทธิ์แอลฟาของครอนบาคเท่ากับ 0.81 วิเคราะห์ข้อมูลโดยใช้ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และวิเคราะห์ความแปรปรวนทางเดียวผลการวิจัยพบว่า ทัศนคติต่อวิชาชีพพยาบาลโดยรวมอยู่ในระดับดี ( = 3.50) เมื่อพิจารณารายด้านพบว่าด้านความเชื่อและความคิดอยู่ในระดับปานกลาง ( = 3.47) ด้านความรู้สึกอยู่ในระดับดี ( = 3.66) ด้านพฤติกรรมอยู่ในระดับปานกลาง( = 3.37) และพบว่า กลุ่มตัวอย่างที่แผนการเรียนแตกต่างกันมีทัศนคติต่อวิชาชีพพยาบาลไม่แตกต่างกันที่ระดับนัยสำคัญทางสถิติ .05 จากการวิจัยครั้งนี้แสดงให้เห็นว่ามุมมองของกลุ่มตัวอย่างต่อวิชาชีพพยาบาลมีแนวโน้มไปทางด้านบวก และไม่แตกต่างกันในแต่ละกลุ่มแผนการเรียน และจากการแสดงความคิดเห็นกลุ่มตัวอย่างให้ความคิดเห็นในด้านจุดเด่นของวิชาชีพคือ วิชาชีพพยาบาลมีหน้าที่ในการดูแลและให้ความช่วยเหลือผู้ป่วย ผู้ประกอบวิชาชีพพยาบาลเป็นผู้มีความเมตตาและผู้ประกอบวิชาชีพพยาบาลเป็นผู้มีความอดทน ด้านข้อเสนอแนะที่ควรพัฒนา คือ ควรปลูกฝังให้บุคลากรมีความรักในวิชาชีพพยาบาลควรยิ้มแย้มเวลาให้บริการผู้ป่วยที่มารับบริการ และวิชาชีพพยาบาลได้รับค่าตอบแทนไม่เหมาะสมกับภาระงาน ซึ่งเป็นสิ่งที่สถาบันการศึกษาพยาบาลและผู้ที่เกี่ยวข้องควรตระหนักถึงและนำมาใช้เป็นแนวทางในการพัฒนาวิชาชีพพยาบาลต่อไป The Attitude Toward Nursing Profession among The Generation Z Population: The Secondary School Case Study This descriptive research was aimed to explore Generation Z population’s attitudes toward nursing profession and compare attitudes in difference education program. Two hundred and ffty-one students studying in Grade 12 in academic year 2016 at the secondary school level were selected by using Stratifed random sampling. The participants were invited to complete the Questionnaire of attitude toward nursing profession. The validity of the Questionnaire was conducted by 3 experts, and the Cronbach’s alpha coeffcient was 0.81. The data were analyzed using mean, standard deviation and one way ANOVA. The results revealed that an overall of the subjects’ score of attitude toward nursing profession was in a good level. ( = 3.50) For each part of attitudes, the study found that the cognitive component was in a moderate level. ( = 3.47) The affective component was in a good level. ( = 3.66) The behavioral component was in a moderate level. ( = 3.37) The study was also found that there was no signifcantly difference between attitude toward nursing profession and education program. (p>.05) This study indicated that an overall attitude toward nursing profession was in a good level. The participants provided positive feedback on strengths of nursing profession which focused on the responsibilities of nurses, compassion, caring, empathy and helping patients with deep heart. This fndings would not only help nursing educators fully understand the educational effects of nursing profession, but also provide recommendations for nursing schools in their efforts to recruit the new generation population and develop positive attitudes and professional values of nursing in order to establish the foundation for future nursing career. Moreover, reasonable salary was considered.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">